Wetland Management Reduces Sediment and Nutrient Loading to the Upper Mississippi River. Issue 2 (1st March 2013) - Kreiling, Rebecca M.; Schubauer‐Berigan, Joseph P.; Richardson, William B.; Bartsch, Lynn A.; Hughes, Peter E.; Cavanaugh, Jennifer C.; Strauss, Eric A.
Abstract : Restored riparian wetlands in the Upper Mississippi River basin have potential to remove sediment and nutrients from tributaries before they flow into the Mississippi River. For 3 yr we calculated retention efficiencies of a marsh complex, which consisted of a restored marsh and an adjacent natural marsh that were connected to Halfway Creek, a small tributary of the Mississippi. We measured sediment, N, and P removal through a mass balance budget approach, N removal through denitrification, and N and P removal through mechanical soil excavation. The marsh complex had average retention rates of approximately 30 Mg sediment ha −1 yr −1, 26 kg total N ha −1 yr −1, and 20 kg total P ha −1 yr −1 . Water flowed into the restored marsh only during high‐discharge events. Although the majority of retention occurred in the natural marsh, portions of the natural marsh were hydrologically disconnected at low discharge due to historical over‐bank sedimentation. The natural marsh removed >60% of sediment, >10% of P, and >5% of N loads (except the first year, when it was a N source). The marsh complex was a source of NH4 + and soluble reactive P. The average denitrification rate for the marsh complex was 2.88 mg N m −2 h −1 . Soil excavation removed 3600 Mg of sediment, 5.6 Mg of N, and 2.7 Mg of P from the restored marsh. The marsh complex was effective in removing sediment and nutrients from storm flows; however, retention could be increased if more water was diverted into both restored and natural marshes before entering the river.